2009
DOI: 10.1371/journal.pgen.1000640
|View full text |Cite
|
Sign up to set email alerts
|

A Role for E2F Activities in Determining the Fate of Myc-Induced Lymphomagenesis

Abstract: The phenotypic heterogeneity that characterizes human cancers reflects the enormous genetic complexity of the oncogenic process. This complexity can also be seen in mouse models where it is frequently observed that in addition to the initiating genetic alteration, the resulting tumor harbors additional, somatically acquired mutations that affect the tumor phenotype. To investigate the role of genetic interactions in the development of tumors, we have made use of the Eμ-myc model of pre-B and B cell lymphoma. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Specifically, we noted a role for E2Fs in an EmMyc lymphomagenesis model (18) and in a K5-Myc skin epithelial model (19). Briefly, in the Em-Myc model, tumors were generated on various E2F mutant backgrounds, illustrating that of the activator E2Fs, only E2F2 altered tumor latency and in opposition to what we observed, loss of E2F2 accelerated tumor formation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Specifically, we noted a role for E2Fs in an EmMyc lymphomagenesis model (18) and in a K5-Myc skin epithelial model (19). Briefly, in the Em-Myc model, tumors were generated on various E2F mutant backgrounds, illustrating that of the activator E2Fs, only E2F2 altered tumor latency and in opposition to what we observed, loss of E2F2 accelerated tumor formation.…”
Section: Discussionmentioning
confidence: 72%
“…Any impact on tumor development in the absence of an E2F should be considered in the light of these findings. Interestingly, a recent study on the role of the E2Fs in Mycinduced tumors in the lymphatic system revealed individual roles for the E2Fs, largely dependent upon the context of expression (18). In short, it was concluded that loss of E2F2 accelerated tumor formation in that tissue.…”
Section: Introductionmentioning
confidence: 99%
“…33 There is no conflict, however, because while the Em-myc mouse is useful to study the role of c-myc in lymphomagenesis, 34 this mouse is not a BL model. Indeed, Em-myc mice develop primarily pre-B-cell tumors whose histopathologic features are consistent with the diagnosis of lymphoblastic lymphoma rather than BL.…”
Section: Discussionmentioning
confidence: 99%
“…Myc further stimulates genes involved in nucleotide metabolism and specifically interacts with the E2F family of transcription factors to drive proliferating cells into S phase for DNA replication (Leone et al 2001;Zeller et al 2006;Rempel et al 2009). As a pleiotropic transcription factor, Myc also directly stimulates cell cycle regulatory genes and those directly involved in DNA replication, such as CDK4, CDK6, and MCM genes .…”
Section: Growth Factor-stimulated Transcriptional Responsesmentioning
confidence: 99%